(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2017)
In this study we aim at investigating the phenomenon of the Mafia infiltration in apparently legal firms (criminal firms), by analyzing their main characteristics. We focus our attention on criminal firms located in Central and Northern Italy, which have been targeted by a police operation (and by subsequent judicial procedures) during the decade 2004-2015. Our analysis shows that Mafia organizations do not use companies only to launder the resources accumulated through illicit activities. Specifically, criminal firms are on average larger, have more debt and lower liquidity than non-criminal ones. Furthermore, we have identified an interesting variability in our sample that reveals the existence of three different types of criminal firms that respond to different needs of the criminal organization. A first group is composed by small firms, which appear to not carry out any productive activity and that are used to support the organization. Then we tracked a second group of small and medium-sized enterprises, which launder money according to the ‘classic’ method. Finally, there are large firms that record high levels of performance and are very similar to ‘clean’ and profitable firms. These firms seem to meet more complex needs related to the establishment of connections with other companies and the infiltration of the political and social spheres. Keywords: Organized crime, Mafia, Performance, Criminal Firms, Corporate Governance